THE INFLUENCE OF RETURN ON EQUITY, DEBT RATIO AND DIVIDEND POLICY ON COMPANY VALUE - Lia Diana; A Khoirul Anam (Universitas PGRI Semarang, 2025)
This study aims to analyze the effect of return on equity, debt equity ratio and dividend payout ratio on firm value. The study was conducted in manufacturing companies in the various industrial sectors for the period 2019-2022. The sampling technique was carried out using the probability sampling method using the criteria of companies listed in the various industrial sectors of the IDX from 2019-2022.. The data analysis method uses STATA. Proxies for return on equity variables use return on equity (ROE), debt ratio using debt equity ratio (DER), dividend policy using dividend payout ratio (DPR). The firm value variable uses price book value (PBV). The results showed that return on equity has a positive effect on firm value, while debt ratio and dividend policy have no effect.